A girl, a dog & some boys - Identity and sense of belonging among Greenlandic youth in Nuuk - Maurtvedt, Tove (Universitetet i Tromsø, 2011)
In classical anthropology and literature in general, the connection between nature and man was a way to perceive cultural adaption, where nature and skills in the Arctic often have received the most attention. Up to a few decades ago, the Greenlanders lived close to nature in rural areas spread around the island. Today most of the population live in towns. The main focus of this thesis looks into the relevance of nature in identity development in the capital Nuuk. The research started out focusing on identity management in relation to nature among youths in the capital of Greenland, Nuuk. By the method participatory video, one gets an understanding how boys perceive on what a good life for them means in Nuuk. The boys’ stories continue with the researcher’s relationship with a teenage girl, her aunt and a dog. We get insight in how they share reflections and knowledge about the natural and city environment. The thesis shows that nature plays an important role in the Greenlanders sense of belonging. Through the researcher’s reflexive approach, meetings and relations with various informants, where informants and the researcher work as each other’s catalysts in the search for meaning, another topic came up. The Greenlandic – Danish relationship was a matter of importance that was impossible to overlook. The thesis reflects upon the Nuuk citizens’ perception of the influences of the modernisation process; It gives insight in how this is expressed and experienced. Finally, this Master’s thesis argues that it depends on the eyes of the person (seeing) how to interpret the city landscape and its surroundings.